Clinico-Epidemiological Study of Canine Mammary Gland Tumours - Rokad, Hardik A.; Bhatt, Raghuvir H.; Talekar, Shivaji H.; Vadalia, Jignesh V.; Padaliya, Nilesh R.; Dodia, Vaibhav D. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to determine the clinico-epidemiological surveillance of canine mammary gland tumours (CMT) during the period 2019-2022 at Veterinary Clinical Complex of the College , Junagadh (India). Total 10712 canine cases were registered during the study period. Among them, 2816 (26.28%) cases were suffered with different surgical ailments. In which, 63 cases (2.24 %) were diagnosed as mammary gland tumours. The overall incidence of canine mammary gland tumours was 0.58 % during the study period. Age-wise incidence of CMT was highest in 5 to 8 years old bitches (26 cases, 41.26%), followed by 9 to 12 years (23 cases, 36.50%), less than 4 years (10 cases, 15.87%) and more than 13 years (4 cases, 6.34%). Breed wise distribution showed a higher incidence in German Shepherd (26/63, 41.26%) followed by Labrador Retriever (16/63, 25.39%), Spitz (15/63, 23.80%), Non-descript breed (5/63, 7.93%) and Lhasa Apso (1/63, 1.58%). Clinical observations and diagnosis of affected cases revealed involvement of 89 mammary glands in 63 affected cases. Based on observations, highest frequency was observed in inguinal glands (37/89, 41.57 %) followed by caudal abdominal (25/89, 28.08 %), cranial abdominal (16/89, 17.98 %), caudal thoracic (8/89, 8.98 %) and cranial thoracic (3/89, 3.37 %) glands. This study revealed higher incidence of canine mammary gland tumours in 5 to 8 years of age group and in German Shephard breed. Moreover, inguinal glands were found to be more affected.